Effect of different drying processes on the protein degradation and sensory quality of Layú: a Chinese dry-curing grass carp - Zhang, J.; Fang, Zhongxiang; Cao, Y.; Xu, Y.; Hu, Y.; Ye, X.; Yang, W. (Taylor & Francis, 2013)
Five different drying methods, sun drying, intermittent drying, low-temperature drying at 5°C, low-temperature drying at 15°C, and hot-air drying at 45°C, were comparatively evaluated based on physicochemical properties and sensory properties of dry-cured Layú. Sun drying and intermittent drying Layú showed superior sensory qualities compared with other dried samples. Based on the comprehensive comparison of sensory qualities and safety concerns, intermittent drying Layú was more acceptable compared to other dry-cured Layú and thus was recommended for dry-curing fish products as it could shorten the drying time with relative constant drying rate, increased flavor amino acid content, and fewer safety concerns.